Green-synthesized Mg-substituted PrFeO3 perovskites via waste-derived precursors for acetone gas sensing - Middha, Shiffali; Nindrayog, Amritpal Singh; Mahajan, Jagriti; Tandon, Nitin; Singh, Satvir; Sharma, Indu; Dosanjh, Harmanjit Singh; Singh, Jaspal; Mahajan, Aman; Prasad, Nupur; Varshney, Deekshant; Singh, Lovepreet; et al. (Frontiers in Materials, 2025)
The detection of volatile organic compounds (VOCs), particularly acetone, is crucial for environmental monitoring and biomedical diagnostics. In this study, Mg-substituted PrFeO3 perovskite oxides (PrMgxFe1-xO3, x = 0.1, 0.2, 0.3) were synthesized via a sol-gel auto-combustion route using Fe and Mg precursors extracted from waste-derived materials, offering a sustainable and cost-effective synthesis pathway. Pristine PrFeO3 exhibited p-type semiconducting behavior; however, Mg incorporation induced a shift to n-type conduction, attributed to the generation of oxygen vacancies and Fe3+/Fe2+ charge compensation. Gas sensing measurements conducted between 60 °C and 210 °C identified 150 °C as the optimal operating temperature. The x = 0.3 composition demonstrated the highest response to acetone, with rapid response (33 s) and recovery (20 s) times. The sensor exhibited excellent repeatability at 50 ppm acetone, moderate selectivity toward ethanol, propanol, and DMF, and demonstrated good long-term stability. The VOC sensing performance is attributed to defect engineering via Mg substitution, increased oxygen vacancy concentration, and improved charge carrier dynamics. These results highlight the potential of waste-integrated perovskite sensors in advancing sustainable gas-sensing technologies.